2020
DOI: 10.1016/j.jcmgh.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CFTR Bicarbonate Channel Activity by WNK1: Implications for Pancreatitis and CFTR-Related Disorders

Abstract: Backgraoud & AimsAberrant epithelial bicarbonate (HCO3−) secretion caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene is associated with several diseases including cystic fibrosis and pancreatitis. Dynamically regulated ion channel activity and anion selectivity of CFTR by kinases sensitive to intracellular chloride concentration ([Cl−]i) play an important role in epithelial HCO3− secretion. However, the molecular mechanisms of how [Cl−]i-dependent mechanisms regulate CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The bicarbonate ion is larger than chloride ion and according to molecular dynamic simulations, the D1152H substitution may introduce a barrier to the internal vestibule that specifically affects bicarbonate ion access. The relative permeability of the pore to bicarbonate ions is also dependent on intracellular chloride ion concentrations and WNK1-SPAK signaling [ 38 , 42 , 43 ]. It remains possible that the D1152H substitution alters the interaction of CFTR with this signaling pathway and this concept will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The bicarbonate ion is larger than chloride ion and according to molecular dynamic simulations, the D1152H substitution may introduce a barrier to the internal vestibule that specifically affects bicarbonate ion access. The relative permeability of the pore to bicarbonate ions is also dependent on intracellular chloride ion concentrations and WNK1-SPAK signaling [ 38 , 42 , 43 ]. It remains possible that the D1152H substitution alters the interaction of CFTR with this signaling pathway and this concept will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This WNK1 effect was not dependent on SPAK and OSR1 and did not affect CFTR expression or trafficking, but affected the physical property of the CFTR channel. 87 Finally, Hoegger and colleagues demonstrated that pharmacologic inhibition of NKCC1 in pig airway epithelial cell led to the secretion of a viscid mucus that remained attached to the epithelium in the absence of bicarbonate. 88 These observations indicate that NKCC1 and CFTR dysfunction may share common underlining mechanisms that need to be further explored.…”
Section: Nkcc1 “Knockout” Patientsmentioning
confidence: 99%
“…Moreover, the amount of CFTR is rate-limiting for HCO 3 − transport in contrast to Cl − secretion, which nearly reaches the WT level in CFTR+/F508del pig epithelia [ 28 ]. In addition, a low intracellular Cl − concentration may switch CFTR from a predominant Cl − channel to a predominant HCO 3 − channel, by activating intracellular Cl − -sensitive kinases (with-no-lysine kinase WNK1, oxidative stress-responsive kinase 1, OSR1, and sterile 20/SPS1-related proline/alanine-rich kinase, SPAK) [ 108 , 109 ]. Although this has been shown in pancreatic cells, this may be a mechanism that is also in place in the lung, as WNK1 and OSR1 are largely present in the lung [ 110 ].…”
Section: Bicarbonate Transport In Airway Cellsmentioning
confidence: 99%
“…Although this has been shown in pancreatic cells, this may be a mechanism that is also in place in the lung, as WNK1 and OSR1 are largely present in the lung [ 110 ]. Interestingly some CFTR mutations located in transmembrane domains selectively decrease the transport of HCO 3 − by hindering the physical association between CFTR and WNK1 [ 109 , 111 , 112 ]. Third, HCO 3 − transport is often assessed indirectly, i.e., by measuring pH changes in experimental protocols.…”
Section: Bicarbonate Transport In Airway Cellsmentioning
confidence: 99%